2022
DOI: 10.1002/cbin.11840
|View full text |Cite
|
Sign up to set email alerts
|

Calycosin suppresses colorectal cancer progression by targeting ERβ, upregulating PTEN, and inhibiting PI3K/Akt signal pathway

Abstract: High intake of phytoestrogen has been reported to be associated with the prevention of colorectal cancer (CRC). Calycosin belongs to the phytoestrogen that has been shown to suppress CRC cells in our previous study. However, its anticancer activity and molecular mechanisms have not been elucidated. In this study, we analyzed the effect of calycosin on the viability and apoptosis of human CRC HCT116 and SW480 cells via MTT assay, flow cytometry assay, and caspase-3/7 activity assay. The protein expressions of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…In addition, the anti-tumour effect of ISL, as a typical phytoestrogen, has been found to be related to oestrogen receptors [ 26 , 27 , 28 ]. It has been found that oestrogen receptors can participate in tumour growth and metastasis by regulating the PI3K signalling pathway [ 29 ]. ESR2 (oestrogen receptor beta), PIK3CG (phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit gamma) and GSK3β (glycogen synthase kinase three beta), the predicted common drug–disease targets, are typical targets involved in the oestrogen signalling pathway and the PI3K/AKT pathway.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the anti-tumour effect of ISL, as a typical phytoestrogen, has been found to be related to oestrogen receptors [ 26 , 27 , 28 ]. It has been found that oestrogen receptors can participate in tumour growth and metastasis by regulating the PI3K signalling pathway [ 29 ]. ESR2 (oestrogen receptor beta), PIK3CG (phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit gamma) and GSK3β (glycogen synthase kinase three beta), the predicted common drug–disease targets, are typical targets involved in the oestrogen signalling pathway and the PI3K/AKT pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Lin Zu demonstrated that calycosin could suppress the growth of xenograft mouse tumors by inhibiting the PI3K/Akt signaling pathway and increasing ER-β using siRNA and PTEN. 68 Another study led by Zhao X. showed that ERβ, a mediator of the stimulation of ER-alpha, IGF-1R, p-Akt, and miR-95 expression, can suppress the proliferation of CRC cells caused by calycosin (0-80 μM) in both in vitro and in vivo model. 69 Chen J. et al declared their finding calycosin (0-100 μM) reduced cell proliferation, induced apoptosis, and upregulated of PTEN due to an elevation in ER-β as evaluated by MMT assay, flow cytometry, transwell invasion test, and mRNA levels by rt-PCR.…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 99%
“…Calycosin has been proven via a number of studies to slow the progression of colorectal cancer cell. Lin Zu demonstrated that calycosin could suppress the growth of xenograft mouse tumors by inhibiting the PI3K/Akt signaling pathway and increasing ER‐β using siRNA and PTEN 68 . Another study led by Zhao X. showed that ER‐β, a mediator of the stimulation of ER‐alpha, IGF‐1R, p‐Akt, and miR‐95 expression, can suppress the proliferation of CRC cells caused by calycosin (0–80 normalμM) in both in vitro and in vivo model 69 .…”
Section: Evidence Of Anti‐cancer Perspectives Regarding Calycosinmentioning
confidence: 99%
“…20 Calycosin, a major isoflavonoid in Radix Astragali, exhibits potent anti-inflammatory and antioxidant properties. 21 In addition, calycosin exhibits various anticancer properties [22][23][24] ; its mechanism of action, however, is not well understood.…”
Section: Introductionmentioning
confidence: 99%